Media on democracy services - Łuczak, Marek (Political Preferences, 2017)
Contemporary media plays an increasingly important role in society. Indubitable this process is driven by globalization, but also the democratization of public life. The media are the fruit of democracy, but also its guarantor. This situation, on the one hand, should be treated as a chance, but on the other hand we can also talk about threats. The author of this article raises questions about the models postulated in the interest of the subject and pathology. Key words: democracy, mass media, participation, public control of power